Pengaruh Pemberian Edukasi Berbasis Application Learning Beydi (Berdaya Diri) terhadap Pengetahuan Pencegahan Kekerasan Seksual di SMPN 3 Lamongan - Bilal Sholeh Hudin; Arifal Aris; Suhariyati Suhariyati (Lembaga Pengembangan Kinerja Dosen, 2025)
Sexual violence among adolescents is an increasingly serious issue, exacerbated by limited knowledge and lack of education, which heightens their vulnerability. One innovative approach to addressing this problem is the use of educational applications such as BEYDI (Self-Empowerment), designed to enhance adolescents’ awareness and knowledge of sexual violence prevention. This study aimed to determine the effect of BEYDI application-based education on students’ knowledge regarding sexual violence prevention at SMPN 3 Lamongan. The study employed a pre-experimental design with a one-group pretest-posttest approach. The population consisted of 63 eighth-grade students from classes 8A and 8B, selected through total sampling. Data were collected using pretest and posttest questionnaires and analyzed using the Wilcoxon test. The results indicated a significant increase in students’ knowledge after receiving the educational intervention via the BEYDI application (p < 0.05). It can be concluded that the BEYDI app-based education was effective in enhancing students’ knowledge of sexual violence prevention and can be considered an interactive and efficient alternative educational tool in the school setting.